Improving Cooperation of Children Through Ludo Board Games - Ade Nisfu Ramadhani; Masganti Sit (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACT. Early childhood often faces various developmental challenges, one of which is the ability to work together. Problems such as individualism, difficulty interacting, and lack of empathy towards peers are obstacles that are often found in children at this age. Cooperation is the ability to work collaboratively to complete a task with others. Working together teaches children to prioritize the interests of the Group[A1] s interest their own. The potential to collaborate with children from Hubbul Walad Kindergarten, Serdang Bedagai, is underdeveloped. This is shown ol the fact that children prefer to be alone rather than with their peers. The purpose of this study was to develop the cooperation skills of anal rights at Hubbul Walad Kindergarten in Serdang Bedagai by using ludo board toys. The subjects of this study were 20 children from group B, aged 5-6 years. Data was collected through direct observation, work demonstration, and documentation. According to the research findings, the cooperative capacity of group b students at Hubbul Walad Kindergarten in Serdang Bedagai increased during the 2023/2024 school year by playing group b puzzle games. This is supported by the pre-cycle findings, which showed a percentage of 31.9%. Furthermore, children's cooperative ability grew to 52.2% in the first cycle, representing an increase of 20.3% compared to the previous 3 cycles. Then, in the second cycle, this increased significantly to 85%, or 32.8%, when compared to the children's ability in the first cycle. As a result, the ludo board game can strengthen the cooperative ability of group b students at Hubbul Walad Kindergarten in Serdang bedagai.Keywords: cooperation, games[A2] early childhoodABSTRAK. Anak usia dini sering menghadapi berbagai tantangan perkembangan, salah satunya adalah kemampuan untuk bekerja sama. Masalah seperti individualisme, kesulitan berinteraksi, dan kurangnya empati terhadap teman sebaya menjadi hambatan yang sering ditemukan pada anak-anak di usia ini. Kerja[A3] sama adalah kemampuan untuk bekerja secara kolaboratif untuk menyelesaikan tugas dengan orang lain. Bekerja sama mengajarkan anak-anak untuk memprioritaskan kepentingan kelompok daripada kepentingan merc sendiri. Potensi untuk berkolaborasi dengan anak-anak dari TK Hubbul Walad, Serdang Bedagai, belum berkembang. Hal ini ditunjukkan ol fakta bahwa anak- anak memilih untuk sendiri daripada dengan teman sebaya mereka. Tujuan dari penelitian ini adalah untuk mengembangkan keterampilan kerja sama anal hak di TK Hubbul Walad di Serdang bedagai dengan menggunakar mainan papan ludo. Subjek penelitian ini adalah 20 anak dari kelompok B, berusia 5-6 tahun. Data dilakuka melalui observasi langsung, demonstrasi kerja, dan dokumentasi. Menurut temuan penelitian, kapasitas kerja sama siswa kelompok b di TK Hubbul Walad di Serdang Bedagai meningkat selama tahun ajaran 2023/2024 dengan bermain permainan menyusun teka-teki kelompok b. Hal ini didukung oleh temuan pra-siklus, yang menunjukkan persentase 31,9%. Selanjutnya, kemampuan kooperatif anak tumbuh menjadi 52,2% pada siklus pertama, mewakili peningkatan 20,3% dibandingka 3iklus sebelumnya. Kemudian, pada siklus II, hal ini meningkat signifikan menjadi 85%, atau 32,8%, jika dibandingkan dengan kemampuan anak pada siklus I. Alhasil, permainan papan ludo dapat memperkuat kemampuan kooperatif siswa kelompok b di TK Hubbul Walad di Serdang bedagai.Kata kunci: kerjasasama, permainan early childhood